2014
DOI: 10.9790/0853-131040613
|View full text |Cite
|
Sign up to set email alerts
|

The bright future of dentistry with cold plasma – Review

Abstract: Plasma is the fourth state of matter and other states of matter are liquid, gas, and solid 4. Plasma occurs as a natural phenomenon in the universe in the form of fire, in the polar aurora borealis and in the nuclear fusion reactions of the sun and also can be created artificially which has gained importance in the fields of plasma screens or light sources 1. There are two types of plasma: thermal and non-thermal or cold atmospheric plasma. Thermal plasma has electrons and heavy particles (neutral and ions) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…These were in accordance with many researches (5,27,28) . Valverde et al (29) found a significant increase in the bond strength to zirconia surfaces when cold plasma was applied alone or in combination with alumina sandblasting.…”
Section: Discussionsupporting
confidence: 92%
“…These were in accordance with many researches (5,27,28) . Valverde et al (29) found a significant increase in the bond strength to zirconia surfaces when cold plasma was applied alone or in combination with alumina sandblasting.…”
Section: Discussionsupporting
confidence: 92%
“…7,15,20,22,24,29,30,36,37 Recently, it has been suggested that the application of plasma can lead to enhanced zirconia-resin bonding by making changes on the surfaces of Y-TZP. [31][32][33] In the present study, we assessed the effects of various types of non-thermal plasmas on Y-TZP in terms of surface properties and bonding strength. Surface energy (SE) is a term that expresses the intermolecular forces on the surface of a material and it depends on the values of the polar and disperse components of surface.…”
Section: Discussionmentioning
confidence: 99%
“…32 It has been suggested that plasma modification of surfaces can improve zirconia-resin bonding performance by changing functional groups on the surface creating reactive sites on surfaces. 31,33 Valverde et al reported that application of non-thermal plasma for zirconia ceramic surface treatment significantly increases the micro tensile bond strength. 31 The objectives of the present study were to (1) evaluate surface properties of Cercon ® zirconia ceramics, (2) specify the impact of non-thermal plasma on zirconium bonding strength to resin composite cements.…”
Section: Introductionmentioning
confidence: 99%
“…These plasmas can be produced in air or with various gases, such as oxygen, helium, argon, and nitrogen. Plasma can be produced by power sources with different frequencies such as low frequency, radio frequency, microwave frequency, high voltage AC or DC, to generate atmospheric and low-pressure glow discharge, corona, magnetron, microwave, gliding arc, plasma jet, and DBD discharge [84][85][86].…”
Section: Non-thermal Plasmamentioning
confidence: 99%